Łagodzenie skutków bezrobocia wśród młodzieży w Polsce w latach 1933–1935. Działalność Stowarzyszenia Opieki nad Niezatrudnioną Młodzieżą - Chylak, Karol (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2012)
Permanent and high unemployment level in Poland of the period between the two World Wars compelled the authorities to take actions resulting in reduction in the dimensions of the problem. The situation aggravated during the period of the great crisis. The action taken by Government in order to reduce an increase in the unemployment rate turned out to be counterproductive as it resulted in a growing number of the youth without work. A labor service was to be a response to this situation. The first labor camps in the Second Republic of Poland were inevitably bound with the person of Silesian voivodship governor, Michał Grażyński and has been formed since February 1932 in Silesia. A potential of this initiative has been noticed in Warsaw immediately. It resulted in taking actions which headed towards control takeover and extension of the action. On November 17th, 1933 a social welfare department established the Unemployed Youth Welfare Association (SOM). A principal goal that has been set for SOM was to take care of the not employed youth, in particular by organizing employment for them. Building centers and labor camps, where the unemployed youths could live, work, improve and complement their professional qualifications was the key instrument to realize the above mentioned strategy. 28.224 volunteers (including 1300 female volunteers) have been given work during the 2-year period of time of an association’s activity. They worked by embankment of the Polish rivers (including Vistula, Warta, San), building roads, railways, dams and working at the request of the local governments as well. Interest in the labor centers shown by the army was one of the actual reasons of their liquidation and resulted in transformation of the labor centers into Blustering Labor Camps.